DINAMIKA BAHASA REMAJA DI ERA DIGITAL: TANTANGAN PENGGUNAAN BAHASA INDONESIA BAKU DALAM KONTEKS PENDIDIKAN MENENGAH - Rulyandi (Maulana Atsani: Jurnal Pendidikan Multidisipliner, 2025)
The digital age has significantly transformed how teenagers communicate, particularly through social media, which fosters the emergence of non-standard language trends. This study aims to examine the dynamics of youth language use in digital spaces and to identify the challenges associated with using standard Indonesian within the context of secondary education. The research was conducted at MTs Negeri 2 Lombok Timur using a descriptive qualitative approach. Data were collected through observations, interviews, and documentation of students’ language practices. The findings reveal that intensive exposure to social media language influences students' linguistic structures, vocabulary choices, and communication styles, resulting in decreased consistency in using standard language in educational settings. The study recommends integrating digital language literacy into the curriculum and strengthening the role of teachers in guiding proper language use across various contexts.